How does transformative social service develop? - Nur Sa’adah Muhamad,; Khairul Akmaliah Adham,; Mohmad Adnan Alias,; Khairul Anuar Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
How does social innovation, in the form of transformative social service, develop within a social organization? In this study, we define social innovations as new ideas that are aimed at meeting social goals, which are typically diffused and mobilized by social organizations through their social services. Although there are a number of established social organizations in Malaysia, little is known about how their services have evolved or are diffused, particularly those that are transformative in nature. This lack of understanding can lead to ineffectiveness of social innovation implementation and might compromise the achievement of the intended social purpose. Using the integrated perspectives of process theories of service development, service innovation and firm development, as well as the concept of transformative service, this qualitative historical-processual case study explained the development of transformative services of Majlis Amanah Rakyat (MARA) (translated as the Council of Trust for the People), a prominent Malaysian social organization, from its inception in 1965 until present. Data were collected through in-depth interviews of key people of MARA as well as through analyses of published documents. The study found that MARA’s three foundational services of entrepreneurship development, education and investment have evolved over time in stages, together with the development of MARA as an organization. The services were developed based on the blueprints set out by MARA and the national policy since the early days. These findings establish the link between the concept of innovation and service development to social firms development, and thus overcome some managerial and policy issues of promoting effective management and institutionalization of social organizations.